2008
DOI: 10.1007/s00018-008-8290-0
|View full text |Cite
|
Sign up to set email alerts
|

Signaling mechanisms of neurite outgrowth induced by the cell adhesion molecules NCAM and N-Cadherin

Abstract: Formation of appropriate neural circuits depends on a complex interplay between extracellular guiding cues and intracellular signaling events that result in alterations of cytoskeletal dynamics and a neurite growth response. Surface-expressed cell adhesion molecules (CAMs) interact with the surroundings via the extracellular domain and bind to the cytoskeleton via their intracellular domain. In addition, several CAMs induce signaling events via direct interactions with intracellular proteins or via interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
115
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 104 publications
2
115
0
Order By: Relevance
“…Variable roles of JLP and N-cadherin according to the differential cellular context have been demonstrated in previous studies. For example, JLP has been reported to negatively regulate NGFinduced neurite outgrowth via JNK inhibition during neuronal differentiation (36) as opposed to the previous report demonstrating that N-cadherin is involved in NGF-induced neurite outgrowth (37). Thus, the association between N-cadherin and JLP may be involved in differential cell fate by modulating signaling pathways including p38 MAPK and JNK according to the cellular context.…”
Section: Discussionmentioning
confidence: 85%
“…Variable roles of JLP and N-cadherin according to the differential cellular context have been demonstrated in previous studies. For example, JLP has been reported to negatively regulate NGFinduced neurite outgrowth via JNK inhibition during neuronal differentiation (36) as opposed to the previous report demonstrating that N-cadherin is involved in NGF-induced neurite outgrowth (37). Thus, the association between N-cadherin and JLP may be involved in differential cell fate by modulating signaling pathways including p38 MAPK and JNK according to the cellular context.…”
Section: Discussionmentioning
confidence: 85%
“…ECM remodeling and changes in cellular interactions with the ECM are important for the initiation of EMT (35). Integrin complexes enable cells to receive signals from ECM proteins through interaction with signal mediators, including integrin-linked kinase (ILK) and parvin (41,43). Following treatment of U87 cells with TGF-β1 for 72 h, there was a slight increase in ILK expression (1.2-fold) and no detectable change in parvin-α levels, whereas the protein level of parvin-β was decreased (0.66-fold).…”
Section: Discussionmentioning
confidence: 99%
“…These events have not been thoroughly characterized but are hypothesized to occur both via direct activation of downstream signaling cascades and via interactions with other cell surface receptors such as FGFRs (Hansen et al, 2008a). In an in vitro study by Christensen et al, (2006) using recombinant NCAM (F3 module 1-2) and FGFR2 (Ig module 2-3) proteins it was shown that the binding between the recombinant proteins had Kd values similar to that of NCAM-FGFR1 binding indicating that NCAM might activate FGFR2 in a similar manner as it activates FGFR1.…”
Section: Resultsmentioning
confidence: 99%
“…5B). It has been speculated that NCAM participates in FGFR-induced signaling by binding to PLC, thereby bringing FGFR and PLC into close proximity of each other (Hansen et al, 2008a). However, a direct interaction between NCAM and FGFR1 was demonstrated only recently by surface plasmon resonance and nuclear magnetic resonance (Hansen et al, 2008b, Kiselyov et al, 2003.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation